2019
DOI: 10.1186/s12879-019-4449-6
|View full text |Cite
|
Sign up to set email alerts
|

A cluster-randomised controlled trial comparing school and community-based deworming for soil transmitted helminth control in school-age children: the CoDe-STH trial protocol

Abstract: Background Current guidelines and targets for soil-transmitted helminth (STH) control focus on school-based deworming for school-age children, given the high risk of associated morbidity in this age group. However, expanding deworming to all age groups may achieve improved STH control among both the community in general and school-age children, by reducing their risk of reinfection. This trial aims to compare school-based targeted deworming with community-wide mass deworming in terms of impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…However, many DM programmes in SSA utilize school settings, typically because SAC are thought to be a group with the highest intensity of worm infection [ 54 ]. Additionally, it has been proven that school-based targeted deworming programmes provide an opportunity for STH control efforts while utilizing an existing school-based infrastructure to reach a large proportion of SAC, with teachers acting as drug distributors [ 55 ]. Moreover, research has demonstrated that when older children are treated with DM, worm infections become less prevalent not only for them, but also for household contacts who reside in the same environment as treated children [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, many DM programmes in SSA utilize school settings, typically because SAC are thought to be a group with the highest intensity of worm infection [ 54 ]. Additionally, it has been proven that school-based targeted deworming programmes provide an opportunity for STH control efforts while utilizing an existing school-based infrastructure to reach a large proportion of SAC, with teachers acting as drug distributors [ 55 ]. Moreover, research has demonstrated that when older children are treated with DM, worm infections become less prevalent not only for them, but also for household contacts who reside in the same environment as treated children [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data also highlights the unique challenges when working with non-fecal samples, including the larger proportion of human reads that effectively decrease sequencing depth and the lower biomass which accentuates signal from potential contamination. Petrof et al, 2013;Levin et al, 2016;Sinha et al, 2017;Chapagain et al, 2019;Clarke et al, 2019 Qiagen MagAttract PowerSoil DNA KF Kit (Earth Microbiome Protocol) Easson and Thacker, 2014;McDonald et al, 2016;Halfvarson et al, 2017;Marotz et al, 2017;McDonald et al, 2018 ZymoBIOMICS Terranova et al, 2018;Wurm et al, 2018;Zabat et al, 2018;Gibson et al, 2019;Reinhart et al, 2019 *This list is not exhaustive. Example references include five studies from a variety of journals, study types, and sample types.…”
Section: Discussionmentioning
confidence: 99%
“…Current national guidelines for STH control are focused on school-based deworming [ 17 ]. Expanding deworming to all age groups has been noted as a benefit to communities in general and, in particular, to school-age children, by reducing their risk of reinfection [ 32 ]. Our study included a particular age group not included in the eligible priority age group established by national guidelines to receive the low-cost single dose [ 17 ].…”
Section: Discussionmentioning
confidence: 99%